2004
DOI: 10.1111/j.1365-2516.2004.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion of B‐domain deleted recombinant factor VIII (ReFacto) in patients with haemophilia A undergoing surgery: clinical experience

Abstract: This retrospective, open-label, non-comparative study evaluated continuous infusion of recombinant factor VIII (ReFacto), B-domain deleted recombinant FVIII (BDDrFVIII), in patients with haemophilia A undergoing surgery and requiring >5 consecutive days of treatment. Sixteen patients from eight centres underwent a total of 20 procedures. Haemostatic outcome was assessed as 'excellent' or 'good' in 75% of procedures, and target FVIII:C levels were maintained throughout the continuous infusion period. The report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
6
27
0
1
Order By: Relevance
“…Unfortunately, in all these studies, only the FVIII loading dose was based on an individual PK-profile obtained several days before surgery. [30][31][32][33][34][35] Iterative perioperative FVIII dosing-adjustments after first loading dose could not be performed as there was no population PK model. The perioperative population PK model presented here will now make Bayesian adaptive dosing in this setting possible.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in all these studies, only the FVIII loading dose was based on an individual PK-profile obtained several days before surgery. [30][31][32][33][34][35] Iterative perioperative FVIII dosing-adjustments after first loading dose could not be performed as there was no population PK model. The perioperative population PK model presented here will now make Bayesian adaptive dosing in this setting possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was difficult to judge the continuous infusion rate and clearance. The initial infusion rate in previous studies [2,5,13–15] was from 1.8 to 6.0 IU kg −1 h −1 , and the average clearance of FVIII in previous studies [1,4,16] was from 2.65 to 3.89 mL kg −1 h −1 . In the above results, there are only three reports that described the clearance and infusion rate for a single product during some kinds of surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…In our case the patient was affected by severe hemophilia A and admitted to hospital for cardiac revascularization made by double bypass internal mammary artery -coronary artery. According to international guidelines and published studies, to control haemostasis the patient was treated during surgery and for thirteen postoperative days with continuous infusion of recombinant FVIII B-domain deleted [5,6]. A published review by Sharathkumar et al showed that inhibitor development [7] is a possible complication of continuous infusion of coagulation factor, but in our case the laboratory tests excluded this hypothesis.…”
Section: Discussionmentioning
confidence: 83%